The Bedrock of Rock Art: The Significance of Quartz Arenite as a Canvas for Rock Art in Central Sweden - Löfstedt Joakim; Löwenborg Daniel (Open Archaeology)
In Scandinavia, numerous regions with high densities of rock art exist. One notable area is Mälardalen in central Sweden, where rock art, primarily dating from the Bronze Age and featuring various characters and symbolic meanings, is located along the prehistoric Lake Mälaren coastline. This article examines the landscape locations of these carvings in order to identify their distribution patterns. The methods employed include spatial analysis with geographic information system combined with Maxent, a machine learning technique. Geospatial data on the environment, particularly the bedrock, along with information about archaeological sites and the number of carvings, were analyzed. The primary findings reveal a significant correlation between rock art and quartz arenite. Despite covering only 1.6% of the land area in Mälardalen, this bedrock type hosts half of the known rock art. In this study, rock art is defined as images depicting various figures, such as ships, while cup marks are analyzed separately. The study argues that there has been a significant preference for specific rock types in the creation or preservation of rock art. The rock must be sufficiently soft to allow for carvings, yet hard and stable enough to withstand weathering.